A) I included a graph, look below.
B)
Input the y in x = y + 3.
x = (-4x - 3) + 3
x = -4x + 0
Add 4x to both sides.
5x = 0
Divide both sides by 5.
x = 0
Input that x value in y = -4x - 3
y = -4(0) - 3
y = 0 - 3
y = -3
(0, -3)
C)
Convert both equations to Standard Form.
x = y + 3
Subtract y from both sides.
x - y = 3
y = -4x - 3
Add 4x to both sides.
4x + y = -3
Add the equations together.
4x + y = -3
x - y = 3
equals
5x = 0
Divide both sides by 5.
x = 0
Input that into one of the original equations.
0 = y + 3
Subtract 3 from both sides.
-3 = y
(0, -3)
3. It has 3 symmetrical lines, so, therefore, has 3 lines of reflectional symmetry.
Hope this helps!
<em>~cupcake </em>
It is b Latasha charges 10 dollars before she begins to work
Answer:
no hablo ingles
Step-by-step explanation:
??y voy a 5c